Respuesta :

Consider, pls, this option.
Please, change the design according to local requirements.
Ver imagen evgeniylevi

The general solution of the given differential equation. y'' + 2y' + 5y = 3 sin 2t is y = e^(-t) * [ A cos(2t) + B sin(2t) ] + (-12/17) * cos(2t) + (3/17)*sin(2t)

How to compue the equation?

y'' + 2y' + 5y = 3sin(2t)

Auxiliary equation

m^2 + 2m + 5 = 0

m = -1 + 2i, -1 - 2i

yc = e^(-t) * [ A cos(2t) + B sin(2t) ]

let yp = C*cos(2t) + D*sin(2t)

yp' = -2C*sin(2t) +2 D*cos(2t)

yp'' = -4C*cos(2t) - 4D*sin(2t)

yp'' + 2yp' + 5yp = 3sin(2t)

= -4C*cos(2t) - 4D*sin(2t) + 2 * [-2C*sin(2t) +2 D*cos(2t)] + 5 * [C*cos(2t) + D*sin(2t)] = 3sin(2t)

= -4C*cos(2t) - 4D*sin(2t) - 4C*sin(2t) + 4 D*cos(2t) + 5C*cos(2t) + 5D*sin(2t) = 3sin(2t)

= - 4C*sin(2t) + 4 D*cos(2t) + C*cos(2t) + D*sin(2t) = 3sin(2t)

Compare like terms

D - 4C = 3

4D + C = 0 => C = -4D

From D -4C = 3

D - 4*(-4D) = 3

17D = 3

D = 3/17

C = -12/17

Therefore, the general solution of the given differential equation. y'' + 2y' + 5y = 3 sin 2t is y = e^(-t) * [ A cos(2t) + B sin(2t) ] + (-12/17) * cos(2t) + (3/17)*sin(2t).

Learn more about equations on:

https://brainly.com/question/13763238

#SPJ2